2005
DOI: 10.1111/j.1540-5907.2006.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Quality Matter? Challengers in State Supreme Court Elections

Abstract: We assess whether quality challengers in state supreme court elections have a significant impact on the electoral successes of incumbents and whether the electorate seemingly makes candidate-based evaluations in these races. To address these questions, we examine 208 elections to the states' highest courts from 1990 through 2000 in the 21 states using partisan or nonpartisan elections to staff their benches. From a Heckman two-stage estimation procedure that takes into account factors influencing challengers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 54 publications
6
109
1
Order By: Relevance
“…In that case we confound the competence effects of term limits with pre-existing differences in average quality. In order to control for this possibility, we include a variable reflecting the governor's years of political experience prior to becoming governor, which is a standard proxy for a politician's quality, measured at the time of entering office (Bond, Covington, and Fleisher 1985;Hall and Bonneau 2006;Jacobson 1989;Van Dunk 1997). 10 Finally, we include state fixed effects, year fixed effects, and state-specific linear time trends to address any remaining unobserved heterogeneity.…”
Section: Independent Variables and Controlsmentioning
confidence: 99%
“…In that case we confound the competence effects of term limits with pre-existing differences in average quality. In order to control for this possibility, we include a variable reflecting the governor's years of political experience prior to becoming governor, which is a standard proxy for a politician's quality, measured at the time of entering office (Bond, Covington, and Fleisher 1985;Hall and Bonneau 2006;Jacobson 1989;Van Dunk 1997). 10 Finally, we include state fixed effects, year fixed effects, and state-specific linear time trends to address any remaining unobserved heterogeneity.…”
Section: Independent Variables and Controlsmentioning
confidence: 99%
“…In 2004, fifty-five percent of Republicans and forty-five percent of Democrats voted straight tickets in Texas elections (Mack, 2006). The level of uncertainty for voters that Baum discussed seems to be diminishing in recent years because Hall and Bonneau (2006) found that experienced challengers for judicial seats, however, enjoy a higher rate of success against incumbents with the electorate apparently considering the qualifications of the candidate in making their voting decisions.…”
Section: Judicial Elections: An Overview and Discussion Of Important mentioning
confidence: 99%
“…Hall and Bonneau (2006) indicated that quality is related to experience, with both appointed and elected judges generally having extensive experience on the bench or in the legal profession. Surprisingly, the literature does not suggest other proxy measures for candidate quality and experience seems like the best measure logically (compared to something like law school attended, etc.)…”
Section: Judicial Elections: An Overview and Discussion Of Important mentioning
confidence: 99%
“…One of the main areas of concern is the influx of money into judicial elections, which is why there has been increased attention by judicial scholars to the effects of campaign contributions on judicial decision making (Bonneau 2005;Hall and Bonneau 2006). Advocates of an independent judiciary free from electoral pressures cite the growing number of studies showing a relationship between contributions and case outcomes.…”
Section: Previous Literaturementioning
confidence: 99%